An Overview of the Alternative Use of Seaweeds to Produce Safe and Sustainable Bio-Packaging - Lomartire, Silvia (2022)
In modern times, seaweeds have become widely involved in several biotechnological applications due to the variety of their constituent bioactive compounds. The consumption of seaweeds dates to ancient times; however, only from the last few decades of research can we explain the mechanisms of action and the potential of seaweed-derived bioactive compounds, which has led to their involvement in food, cosmetic, pharmaceutical, and nutraceutical industries. Macroalgaederived bioactive compounds are of great importance as their properties enable them to be ideal candidates for the production of sustainable “green” packaging. Diverse studies demonstrate that seaweed polysaccharides (e.g., alginates and carrageenans) not only provide health benefits, but also contribute to the production of biopolymeric film and biodegradable packaging. The dispersion of plastics and microplastics in the oceans provoke serious environmental issues that influence ecosystems and aquatic organisms. Thus, the sustainable use of seaweed-derived biopolymers is now crucial to replace plasticizers with biodegradable materials, and thus preserve the environment. The present review aims to provide an overview on the potential of seaweeds in the production of bioplastics which might be involved in food or pharmaceutical packaging.